2013
DOI: 10.1007/s10856-013-4855-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle size on hardening and handling of a premixed calcium phosphate cement

Abstract: Premixed calcium phosphate cements (pCPC) have been developed to circumvent problems related to mixing and transfer of cements in the operating room. In addition, by using pCPC the short working times generally associated with conventional water-mixed cements are avoided. In this work, the influence of particle size on handling and hardening characteristics of a premixed monetite cement has been assessed. The cements were evaluated with respect to their injectability, setting time and compressive strength. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…They exhibited a rapid setting when immersed in a physiological solution, yielding a hardened bioceramics with a higher mechanical strength, approached the reported strengths of sintered porous HA implants and cancellous bone [691,692,693]. Brushite-forming premixed self-setting formulations have been introduced as well [687,688,698,700,701,702]; they have shorter setting times then the aforementioned apatite-forming ones. In addition, studies appeared on preparation of the premixed monetite-forming formulations [269,270], as well as on premixed macroporous calcium orthophosphate scaffolds reinforced by slow-dissolving fibers (in other words, premixed macroporous concretes) [369].…”
Section: Recent Achievements and Future Developmentsmentioning
confidence: 99%
“…They exhibited a rapid setting when immersed in a physiological solution, yielding a hardened bioceramics with a higher mechanical strength, approached the reported strengths of sintered porous HA implants and cancellous bone [691,692,693]. Brushite-forming premixed self-setting formulations have been introduced as well [687,688,698,700,701,702]; they have shorter setting times then the aforementioned apatite-forming ones. In addition, studies appeared on preparation of the premixed monetite-forming formulations [269,270], as well as on premixed macroporous calcium orthophosphate scaffolds reinforced by slow-dissolving fibers (in other words, premixed macroporous concretes) [369].…”
Section: Recent Achievements and Future Developmentsmentioning
confidence: 99%
“…demonstrated that the dehydrated form of brushite, monetite, is considerably more resistant to hydrolysis and hence may be more rapidly resorbed following implantation . Monetite, however, does not form in aqueous CPC reactions since the rate of brushite crystal growth is significantly faster . The use of a nonaqueous liquid, such as glycerol and polyethylene glycol, have been shown to result in the formation of monetite cement .…”
Section: Discussionmentioning
confidence: 89%
“…Despite monetite being more thermodynamically stable than brushite, it does not form in aqueous cement matrices since the rate of crystal formation is considerably higher for brushite than monetite. To circumvent this, a number of authors have explored the use of nonaqueous formulations, commonly referred to as premixed CPC (pCPC) . Advantageously, such materials may be formulated and stored as a paste that may harden in situ when implanted, which may reduce surgical times.…”
Section: Introductionmentioning
confidence: 99%
“…When measuring the setting time of a pCPC the cement will be considered to have set when a layer of cement thick enough to carry the weight of the needle has been formed. pCPC with similar compositions show setting times (Gillmore needle method) around 30-60 minutes [18,19]; however, at this point most of the cement is still unreacted. Therefore, the authors consider that the method presented for evaluating the setting depth of antibiotics since it could allow for a better knowledge and control over the drug release.…”
Section: Discussionmentioning
confidence: 99%
“…When mixed with water, the basic CPCs normally precipitate into hydroxyapatite, while acidic CPCs normally form brushite as the set phase [15,16]. However, when the acidic CPCs have been prepared as premixed pastes the resulting phase after setting has been shown to be mainly monetite [14,17,18]. It is argued that the method of premixing the cements will cause a higher acidity locally in the cement, which could explain the formation of monetite instead of brushite [19]; however, this has not to the authors' knowledge been studied explicitly.…”
Section: Introductionmentioning
confidence: 99%